Graphite oxide: peculiarities of investigation of this material by physical methods - N.V. Alemasova; D.I. Bugorskaya; V.V. Burkhovetskii; G.K. Volkova; V.A. Glazunova; M.Yu. Zelenskii; M.V. Savoskin (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2023)
It is shown by physical methods that the preliminary preparation of samples affects the structure and properties of graphite oxide and partially reduced graphite oxide. The graphite oxide drying technique as the last synthesis stage determines its morphology and structural properties. At drying by sublimation method, the state of graphite oxide in aqueous suspension before the beginning of the process of self-ordering of its sheets is fixed, the data of X-ray diffraction analysis testifies its X-ray amorphous state, the dried graphite oxide appearance is a light yellow powder. Drying of graphite oxide aqueous suspensions at temperatures above room temperature is accompanied by the ordering of the graphite oxide structure under the action of the surface tension and Van der Waals forces with the dark brown film formation. It is shown by scanning and transmission microscopy methods that the method of separation of partially reduced graphite oxide from glass substrates, on which the product is dried, can lead to the formation of wrinkled or roll-shaped structures. When graphite oxide is examined by transmission electron microscopy, even a short exposure to ultrasound (used in the conventional method of depositing the material on a copper grid prior to examination) results in wrinkling and partial curling of the edges of graphite oxide nanoparticles. Mechanical grinding of graphite oxide leads to disordered graphite oxide structure and to the interplanar spacing increase.